Information systems’ effectiveness and organisational performance: a study among small and medium-sized enterprises in North Kivu Province, DR-Congo - Rodrigue Kalumendo; Paluku Kazimoto; Nirmal Kumar Betchoo (Journal of Applied Research in Technology & Engineering)
This study aims to empirically investigate the concept of information systems’ (IS) effectiveness and its relationship with organisational performance in Small and Medium-Sized Enterprises (SMEs). Based on a literature review, the study identifies three dimensions of IS effectiveness: technological context (system quality and information quality), organisational context (users’ IS knowledge, users’ IS involvement, and top management’s IS support), and environmental context (external expertise). Data were collected from 496 SMEs and analysed using structural equation modelling (SEM) with SmartPLS 4.The results indicate that system quality, top management support, and external expertise significantly influence organisational performance. Specifically, management involvement (β=0.098, p<0.05), system quality (β=0.316, p<0.05), and external expertise (β=0.391, p<0.05) are positively associated with performance, explaining approximately 60% of its variance (R2=0.594). These findings underscore the importance of enhancing IS quality and leveraging external expertise for Congolese Small and Medium Enterprises to improve their performance through effective information system utilisation.